Effect of Arbuscular Mycorrhizal Inoculum Rate on Tomato (Lycopersicum esculenta L.) Seedlings (Bangladesh Journal of Microbiology, 2016)
An experiment on the effect of rate of arbuscular mycorrhiza inoculum in producing tomato seedlings (var. Ratan) were conducted in the seedbed of Soil Science Division, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur, Bangladesh during rabi season of 2007-08 and 2008-09. Seven rates of AM inoculum viz. 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0 kg m-2 were studied on tomato seedlings. Cowdung was used at the rate of 5 kg m-2 as basal. Seeds were sown in 10 cm apart solid lines on 13 November 2007 and 11 November 2008, and the seedlings were thinned down to about 3 cm from seedling to seedling within a week of germination. Ratan was used as the variety of tomato. Biomass yield, seedling height and nutrient uptake by tomato seedlings increased greatly with the use of AM inoculum. Biomass yield of tomato seedlings followed quadratic trend with the increase of AM inoculum rate from 0 to 1.0 kg m-2 in 2007-08 and 0 to 2.0 kg m-2 in 2008-09.Bangladesh J Microbiol, Volume 29, Number 2, Dec 2012, pp 104-108